It's linear and equation of the function is :
f ( x ) = 2x - 1
Step-by-step explanation:
According to this trigonometric function, −C gives you the OPPOSITE terms of what they really are, so be EXTREMELY CAREFUL:
Therefore we have our answer.
Extended Information on the trigonometric function
NOTE: Sometimes, your vertical shift might tell you to shift your graph below or above the <em>midline</em><em> </em>where the amplitude is.
I am joyous to assist you anytime.
Answer:
For number 3 the answer is -4
Answer:
Step-by-step explanation:
If (x + 2) is a factor of a polynomial then ( - 2 ) is the zero of that polynomial ⇒ ( - 2 )³ + 2( - 2 )² + 2( - 2 ) + k = 0 ⇒ k = - 4